BACAAN AL-QUR’AN BERDASARKAN IMAM ‘ASHIM RIWAYAT HAFSH THARIQ ASY-SYATHIBIYYAH - Dede Sulaeman (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2020)
This paper discusses reading the Qur'an based on Imam 'Ashim History of Hafsh Tariq As-Syathibiyyah because many Muslims do not know the Al-Qur'an reading using Imams, History and Tariq (Road) especially Muslims who are in Indonesia in this day and age, who generally consider it normal to this greatest miracle, the Qur'an. Yet to get the revelation of the Qur'an, it takes a very long time and getting it is not easy through the process of enduring the Messenger of Allah, peace be upon him during some Ramadhan in the Cave of Hira. Next, the Qur'an decreases gradually for 23 years, 13 years from the Mecca period and 10 years from the Medina period, which illustrates the lengthy time of the Qur'an's descent. Indonesia is a country where the majority of the population embraces Islam. This country when compared to other countries in the world, is the largest Muslim country. There is no country in the world where the number of Muslims is equal to the number of Muslims in Indonesia. In this archipelago, in huts, surau-surau, pesantren-pesantren, rangkang (name of the level of junior teaching), meunasah-meunasah and madrassas there are efforts to learn the Qur'an and even memorize the Qur'an . In Indonesia, the recitation of the Qur'an that is often used is Imam Hafsh 'An' Ashim Thariq Asy-Syathibiyyah because reading according to Imam Hafsh is easier because Farshul Letters do not change and are in accordance with writing, but only slightly change from reading Al- Qur'an besides Imam Hafsh.